Management of a P3A0 Postpartum Patient with Peripartum Cardiomyopathy (PPCM), Acute Decompensated Heart Failure (ADHF), Respiratory Failure Due to Acute Pulmonary Edema, and Community-Acquired Pneumonia (CAP) in the ICU - Sulistiono, Paulus; Budipratama, Dhany (CoinReads Media Prima, 2025)
Introduction: Acute dyspnea following pregnancy is a rare condition often accompanied by significant comorbidities. Potential causes include pulmonary embolism, amniotic fluid embolism, pneumonia, aspiration, pulmonary edema, and other critical conditions. Pulmonary edema, in particular, may occur during pregnancy or the postpartum period, associated with preeclampsia, peripartum cardiomyopathy (PPCM), pre-existing cardiac disease, tocolytic therapy, or fluid overload. This case report highlights a complex clinical scenario involving these factors. Case Description: We present the case of a 36-year-old woman, P4A0, who developed progressive acute dyspnea six days postpartum following a normal delivery. Her condition rapidly progressed to respiratory failure, necessitating admission to the intensive care unit (ICU) and mechanical ventilation. Physical examination and diagnostic workup revealed acute pulmonary edema secondary to peripartum cardiomyopathy, complicated by acute decompensated heart failure (ADHF) and community-acquired pneumonia (CAP). Following tailored medical therapy, the patient’s condition improved, and she was discharged from the ICU on the fifth day in a stable condition. Conclusion: This case underscores the importance of early recognition and multidisciplinary management of acute dyspnea in the postpartum period, particularly when linked to PPCM, ADHF, and CAP. Timely intervention with mechanical ventilation and targeted therapy can lead to favorable outcomes, emphasizing the need for heightened awareness among clinicians managing postpartum patients.